2017
DOI: 10.1016/j.jsps.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of antimicrobial activities of nitrofurazone analogues containing hydrazide-hydrazone moiety

Abstract: In this research we synthesized and tested for antimicrobial activity 21 nitrofurazone analogues. The compounds we obtained were identified on the basis ofH NMR and C NMR spectroscopy. The screening of antimicrobial properties of synthesized compounds revealed a wide spectrum of antimicrobial activity. Compounds ,, -, and - showed very high bactericidal effect towards spp. ATTC and spp. ATTC (MIC = 0.002-7.81 µg/ml and MBC = 0.002-31.25 µg/ml). The levels of activity of several compounds were far better than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…In our previous research, a series of hydrazide‐hydrazones showed very promising antimicrobial and antifungal activities (Popiołek & Biernasiuk, , , , ; Popiołek, Biernasiuk, et al, ). For instance, a series of nitrofurazone analogues containing hydrazide‐hydrazone moiety synthesized by our group displayed, depending on the compounds and bacterial or fungal strains, higher antimicrobial activity than ciprofloxacin, nitrofurantoin or cefuroxime, which were used as reference substances (Popiołek & Biernasiuk, ). In that research, we used different hydrazides of carboxylic acids and condensed them with 5‐nitro‐2‐furaldehyde (Popiołek & Biernasiuk, ).…”
Section: Introductionmentioning
confidence: 98%
“…In our previous research, a series of hydrazide‐hydrazones showed very promising antimicrobial and antifungal activities (Popiołek & Biernasiuk, , , , ; Popiołek, Biernasiuk, et al, ). For instance, a series of nitrofurazone analogues containing hydrazide‐hydrazone moiety synthesized by our group displayed, depending on the compounds and bacterial or fungal strains, higher antimicrobial activity than ciprofloxacin, nitrofurantoin or cefuroxime, which were used as reference substances (Popiołek & Biernasiuk, ). In that research, we used different hydrazides of carboxylic acids and condensed them with 5‐nitro‐2‐furaldehyde (Popiołek & Biernasiuk, ).…”
Section: Introductionmentioning
confidence: 98%
“…[45] Iproniazide, an isoniazid derivative, originally used as an antituberculosis medicine, showed mood elevation in depressed patients, which makes it the first MAO (monoamine oxidase) inhibitor. [46] Due to the broad spectrum of biological activity, especially antimicrobial activity of isonicotinic acid [44,45] and 1,3,4-oxadiazole derivatives, [10 -15] as well as that of hydrazide-hydrazones, reported by our group earlier, [47][48][49][50][51][52] we decided to combine these two pharmacophores in one chemical structure with the hope of obtaining interesting antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…As well as other NSAIDs, naproxen was reported to be efficient in the prevention of many cancers [3][4][5]. Hydrazide-hydrazones [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and 1,2,4-triazole rings [22][23][24][25][26] have diverse biological activities.…”
Section: Introductionmentioning
confidence: 99%